Morphological and biochemical characterization of Alpinia calcarata rhizomes: characterization of Alpinia calcarata rhizomes - Shibila, K; Aneesha, A K; Suma, A; Anitha, P; Rashmi, C R (Journal of Spices and Aromatic Crops, 2023)
Lesser galangal rhizomes are well known for their anti-inflammatory, anti-microbial and anti-oxidant properties. The aim of the present study was to assess the variability in morphological and biochemical characters of lesser galangal, Alpinia calcarata accessions collected from various South Indian states. The results revealed that accession IC373608 was significantly superior with respect to yield contributing traits including the rhizome length, width, fresh yield and dry recovery (6.02 cm, 2.40 cm, 14.63 g tiller-1 and 33.26% respectively) among the eighteen accessions studied. The biochemical analysis of rhizomes revealed that the maximum volatile oil and oleoresin content were found in the accession IC468880 (0.75%) and IC373608 (34.20%) respectively. The highest values for total phenols, total flavonoids and starch were observed in the accessions IC373608 (115.25 mg GAE.g-1), IC582825 (55.65 mg QE. g-1) and IC210656 (44.05 mg. g-1) respectively. The accession IC550112 (7.90%) recorded the lowest crude fibre content, whereas the highest total terpenoid content was noticed in accession IC210421 (20.25%). The GCMSMS profiling of volatile oil of A. calcarata rhizome showed the presence of 28 compounds in it. Considering all economically important characters, accessions IC373608, IC582825 and IC210421 were found to be superior and can be utilized in future crop improvement programmes.